Shaping Resistive Bend Sensors to Enhance Readout Linearity. (14th November 2012) - Saggio, Giovanni; Lagati, Antonino; Orengo, Giancarlo
Abstract : Resistive bend sensors have been increasingly used in different areas for their interesting property to change their resistance when bent. They can be employed in those systems where a joint rotation has to be measured, in particular biomedical systems, to measure human joint static and dynamic postures. In spite of their interesting properties, such as robustness, low price, and long life, the commercial bend sensors have a response which is not actually linear, as an electronic device to measure bend angles should be, to recover human posture without distortion. In this work, different interfaces for sensor device readout were analyzed and compared from the output response linearity point of view. In order to obtain a sensor characteristic as closer as possible to the ideal linear one, a way to calculate the sensor characteristic with a generalized resistive strip contour, starting from an empiric sheet resistance model, was developed, in order to find what is the more suitable nonuniform geometry.